“Best love – Ann”: Letters from Ann Southam to Rachel Browne - Bernstein, Tamara (Circuit)

(untitled) (Circuit, musiques contemporaines, 2025)
This article introduces forty letters that Toronto composer Ann Southam (1937-2010) wrote to Winnipeg-based choreographer Rachel Browne (1934-2012) between 1995 and 2003, and which Circuit is publishing on its website. Although Browne’s letters to Southam are lost, the surviving half of the correspondence documents an artistically fruitful friendship between two major figures in Canadian music and dance. (Browne was a founding mother of contemporary dance in Canada, while Southam was a pioneer of electronic music and minimalism in Canada, as well as a prolific and gifted composer of music for dance.) Feminism dominates the correspondence, in which we see both women striving to create woman-centred art and lives. The article also comments on their shared love of nature, and contextualizes how Browne used Southam’s music in dances she was creating during this period. The article also sketches the two women’s contrasting origins—Browne’s childhood in Philadelphia, where her Russian Jewish parents passed their socialist ideals on to her; Southam’s upper class upbringing within a prominent Canadian newspaper dynasty.